RUSSIAN INSURANCE MARKET AND ITS DEVELOPMENT STRATEGY IN THE MEDIUM TERM - Denis S. Sokol (Модернизация, инновация, развитие, 2015)
In this paper problem of insurance market development in Russia is considered. The special attention is paid on strategies of its developing if past and future, also ways of insurance activity optimization are recommended.